Characterization of Physical and Mechanical Properties of Tungsten Alloy Surfaces for Electroplasticity-Assisted Dry Cutting Machining - Liu, Jie; Chen, Guangjun; Yu, Zhiwei; Jia, Xiongfei; Huang, Jiashuai (International journal of precision engineering and manufacturing-green technology, 2024)
Tungsten alloy has a wide range of applications in aerospace and defense industry because of its high hardness, high strength and other excellent properties. Tungsten alloys are typical hard-to-machine materials, and the electroplastic effect can improve the machining surface quality of hard-to-machine metal materials. However, the complex thermal–mechanical-electrical coupling generated by the relative motional squeezing of the tool and the workpiece under the electric pulse. It will cause a large difference between the physical and mechanical properties of the surface layer and the substrate material. The size and distribution of the characteristic parameters of the physical and mechanical properties of the machined surface, such as work hardening, residual stress and metamorphic layer, are not clear. Therefore, characterization of the physical and mechanical properties of the surface of W93NiFe alloy for electroplasticity-assisted dry turning machining was carried out in this paper. The results showed that the electrically plastic assisted dry turning process effectively alleviated the degree of work hardening on the machined surface of W93NiFe alloy. but the oxidation of the surface layer of the workpiece was exacerbated by excessive pulse voltage, which resulted in the increase of the surface microhardness again; Compared with conventional dry turning, the application of appropriate pulse voltage can effectively reduce the residual stress on the machined surface of W93NiFe alloy. and in this experiment, the variation of pulse frequency had less effect on the residual stress on the machined surface of W93NiFe alloy; After passing the pulse current, the thickness of the surface metamorphic layer increased significantly with the increase of electrical parameters such as pulse voltage and pulse frequency. but there was no significant effect of the two processing methods on the internal organization of W93NiFe alloy.